Exploring Dried Blood Spot Cortisol Concentrations as an Alternative for Monitoring Pediatric Adrenal Insufficiency Patients: A Model-Based Analysis - Stachanow, Viktoria; Neumann, Uta; Blankenstein, Oliver; Bindellini, Davide; Melin, Johanna; Ross, Richard; Whitaker, Martin J.; Huisinga, Wilhelm; Michelet, Robin; Kloft, Charlotte (Frontiers in Pharmacology, 2022)
Congenital adrenal hyperplasia (CAH) is the most common form of adrenal insufficiency in childhood; it requires cortisol replacement therapy with hydrocortisone (HC, synthetic cortisol) from birth and therapy monitoring for a successful treatment. In children, the less invasive dried blood spot (DBS) sampling with whole blood including red blood cells (RBC) provides an advantageous alternative to plasma sampling. Potential differences in binding/association processes between plasma and DBS, however, need to be considered to correctly interpret DBS measurements for therapy monitoring. While capillary DBS samples would be used in clinical practice venous cortisol DBS samples from children with adrenal insufficiency were analyzed due to data availability and to directly compare and thus understand potential differences between venous DBS and plasma. A previously published HC plasma pharmacokinetic (PK) model was extended by leveraging these DBS concentrations. In addition to previously characterized binding of cortisol to albumin (linear process) and corticosteroid binding globulin (CBG; saturable process), DBS data enabled the characterization of a linear cortisol association to RBC, and thereby providing a quantitative link between DBS and plasma cortisol concentrations. The ratio between the observed cortisol plasma and DBS concentrations varies highly from 2-8. Deterministic simulations of the different cortisol binding/association fractions demonstrated that with higher blood cortisol concentrations a saturation of cortisol binding to CBG was observed, leading to an increase of all other cortisol-binding fractions. In conclusion, a mathematical PK model was developed which links DBS measurements to plasma exposure and thus allows for quantitative interpretation of measurements of DBS samples.